Novel methods for the synthesis and functionalisation of sulfoximines and sulfonimidamides: new pharmacophores for the medicinal chemist’s toolbox - Izzo, Flavia (2019)
Sulfoximines, the monoaza analogues of sulfones, have recently gained considerable recognition as a new and versatile structural motif in the life sciences.Therefore our group, in collaboration with Bayer AG (Berlin), is investigating a simple scalable and efficient methodology to make valuable chiral sulfoximines with control of stereochemistry.